Editorial: Understanding funding and financing of transportation infrastructure - Vanelslander, Thierry; Roumboutsos, Athena; Pantelias, Aristeidis (European Journal of Transport and Infrastructure Research, 2018)
Investment in transport infrastructure is under pressure. On the one hand, the need for maintaining and/or replacing existing assets as well as building new ones is higher than ever. On the other hand, funding either for maintaining existing assets or building new ones, is severely constrained. Earlier literature proposed to combine all the above factors in the form of indicators that can describe the elements of the transport infrastructure delivery system. At the heart of this system lies the business model, which generates funding and attracts financing. System elements are drawn and kept together by the efficiency and flexibility of their contractual governance. An important element that determines the overall functionality of the system is the contextual setting: the implementation and transport mode contexts. This special issue brings together multiple research contributions that showcase the importance of understanding the funding and financing characteristics of transport infrastructure. A key common conclusion is that success or failure is not dependent on a single factor but rather a group of factors, which are not the same for all targeted outcomes. All papers, in their analysis of respective factors, identify “turning points” in their positive or negative effect on project performance.